Solar rebound effects: Short and long term dynamics - Nguyen, Luan Thanh; Ratnasiri, Shyama; Wagner, Liam; Nguyen, Dan The; Rohde, Nicholas (Elsevier, 2024)
Rooftop solar is increasingly promoted as a source of low-carbon household energy; however, there is a plausible concern that solar installations might influence energy consumption patterns in ways that undermine potential environmental benefits. In this study, we examine the impact of residential rooftop solar panels on energy usage in Vietnam. Leveraging a comprehensive and unique panel dataset, we employ a difference-in-differences identification strategy to estimate the effects of solar installation on consumption. Our models reveal that households installing solar panels reduce grid consumption (typically carbon-intensive) by approximately 3.6 %. This reduction occurs concomitantly with an increase in total consumption of around 16 %, indicating a substantial rebound effect from solar panels. Nonetheless, dynamic models suggest a diminishing trend over time for both the decline in grid usage and the rebound effect, leveling off to 1.5 % and 3.5 %, respectively, within one year of solar installation. Acknowledging the marked differences in household consumption behavior and electricity demand dynamics between developing and developed nations, our research provides valuable insights into the understanding of the solar rebound effect and its dynamics over time.